Unique positive solution for a p-Laplacian fractional differential boundary value problem involving Riemann-Stieltjes integral - Chengbo Zhai (AIMS Mathematics, 2020)
In this article, we study a class of p-Laplacian fractional differential boundary value problem involving Riemann-Stieltjes integral. By two fixed point theorems of a sum operator in partial ordering Banach spaces, we get the existence and uniqueness of positive solutions for addressed problem. Moreover, we can make iterative sequences to approximate the unique positive solution. In addition, two examples are given to illustrate the main results.